Strategi Pemberdayaan UMKM Berbasis Ekonomi Syariah dalam Mendukung Penguatan Ekonomi Lokal: Oishi Dimsum di Kota Bengkulu - Nurrahma Hidayah; Eta Arisa; Uswatun Hasanah (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in strengthening the local economy through job creation and increasing community income. In the perspective of Islamic economics, MSME empowerment is not only profit-oriented but also emphasizes values such as justice, honesty, and transparency in business activities. However, studies on Islamic economic-based MSME empowerment strategies in the local culinary sector, particularly among micro-scale businesses in regions such as Bengkulu City, remain limited. This study aims to analyze the strategies of Islamic economic-based MSME empowerment in supporting local economic strengthening at Oishi Dimsum in Bengkulu City. This research employs a qualitative method with a descriptive approach, using observation, in-depth interviews, and documentation as data collection techniques. The results indicate that the strategies include product innovation, the use of digital media, improvement of service quality, and strengthening of business management. The implementation of Islamic economic principles is reflected in the use of halal raw materials, price transparency, and ethical business practices. Furthermore, the business contributes to local economic strengthening by creating employment opportunities and increasing community income. This study concludes that Islamic economic-based MSME empowerment plays an important role in supporting sustainable local economic development.